2020
DOI: 10.1038/s41467-020-19624-w
|View full text |Cite
|
Sign up to set email alerts
|

Two nuclear effectors of the rice blast fungus modulate host immunity via transcriptional reprogramming

Abstract: Pathogens utilize multiple types of effectors to modulate plant immunity. Although many apoplastic and cytoplasmic effectors have been reported, nuclear effectors have not been well characterized in fungal pathogens. Here, we characterize two nuclear effectors of the rice blast pathogen Magnaporthe oryzae. Both nuclear effectors are secreted via the biotrophic interfacial complex, translocated into the nuclei of initially penetrated and surrounding cells, and reprogram the expression of immunity-associated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 54 publications
0
85
0
Order By: Relevance
“…Especially, the structure-based functional inference can bridge the gap across rapidly diverging sequences, leading to new hypotheses. A recent study demonstrated that the two nuclear effectors, MoHTR1 and MoHTR2, bind to the promoters of immunity-related genes in rice and interfere with their expression (50). In our clustering, MoHTR2 along with Nup3, also shown to block plant immunity, belong to Cluster 25 with 9 other members with distant homology (Table S4; Table S5) (51).…”
Section: Resultsmentioning
confidence: 99%
“…Especially, the structure-based functional inference can bridge the gap across rapidly diverging sequences, leading to new hypotheses. A recent study demonstrated that the two nuclear effectors, MoHTR1 and MoHTR2, bind to the promoters of immunity-related genes in rice and interfere with their expression (50). In our clustering, MoHTR2 along with Nup3, also shown to block plant immunity, belong to Cluster 25 with 9 other members with distant homology (Table S4; Table S5) (51).…”
Section: Resultsmentioning
confidence: 99%
“…Fungal pathogens secrete virulence factors or effector proteins to overcome host defenses and to facilitate the infection [37][38][39][40][41]. We characterized the first small-secreted virulence factor in a predatory fungus, the nematode-trapping fungus D. flagrans.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve successful infection, virulent M. oryzae isolates have evolved a strategy to secrete effectors into the rice cell for subverting PTI, leading to effector-triggered susceptibility (ETS).To combat a blast fungus capable of subverting PTI, rice deploys nucleotide-binding site leucine-rich repeat (NLR) proteins to recognize the effectors named avirulence (AVR) proteins. Several AVR proteins have been cloned, including AVR-Pita, AVR-Pi9, and Avr-Pizt [173,174]. Recognition of AVR by NLR promotes strong immune responses referred to as effector-triggered immunity (ETI), which arms rice with a second layer of protection in case of disabled PTI [172].…”
Section: Defence Mechanism Of Rice Against Blast Infectionmentioning
confidence: 99%